John Godfrey Saxe papers - Saxe, John Godfrey, 1816-1887.
Handwritten copy of Saxe's poem, A Poet's Constancy (1875), and a letter (1879 Feb. 22) to Saxe from Robert Bonner.
In part, handwritten copy.
Journalist and poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bonner, Robert, -- 1824-1899 -- Correspondence; American poetry; Journalists; Poets